Études critiques du cerveau sexué - Cynthia Kraus (Revue d'anthropologie des connaissances)
The NeuroGenderings project is reminiscent of an interdisciplinary program called Critical Neuroscience. But the steps towards a feminist/queer Critical Neuroscience are complicated by the problematic ways in which critical neuroscientists conceive of their critical practices. They suggest that we work and talk across disciplines as if neuroscientists were from Mars and social scientists from Venus, assigning the latter to the traditional feminine role of assuaging conflict. This article argues that brain science studies scholars need to clarify how we want to frame our critical practices - a critique of what and for whom? - and promote interdisciplinarity. The challenge is to articulate a critical stance that could not be collapsed into the all-encompassing claims of neuroscience, Critical Neuroscience included. I suggest we shift focus: from enhanced communication to the study of controversies (but also non-controversies, failed controversies, etc.) and conflicts. I explore the productiveness of this shift through two examples: the non-controversial notion of brain plasticity, and the controversial question of whether gender identity formation in intersex people is a function of their brain or their genitals. “Socializing” neuroscience with insights from gender and science studies is good; highlighting the conflicting dimensions of social life in the same gesture is even better.